Pharmacokinetics, safety, and tolerability of single and multiple doses of zuranolone in Japanese and White healthy subjects: A phase 1 clinical trial - Takuhiro Sonoyama; Ryosuke Shimizu; Ryuji Kubota; Yumiko Matsuo; Daiki Okutsu; Hideki Yamanaka; Keiko Takasu; Koichi Ogawa; Tomoko Motomiya (Wiley, 2023)
Abstract Aim This phase 1 study assessed the pharmacokinetics, safety, and tolerability of zuranolone in Japanese and White healthy adults, and Japanese healthy elderly subjects. Methods This single‐center study consisted of three parts. In Part A (randomized, double‐blind), the safety, tolerability, and pharmacokinetics of single dose and 7‐day consecutive multiple doses of zuranolone 10, 20, and 30 mg and placebo were assessed in 36 Japanese adults, 24 White adults, and 12 Japanese elderly (aged 65-75 years) subjects. In Part B (randomized, open‐label, crossover), the effect of food intake on the pharmacokinetics and safety of single‐dose zuranolone 30 mg was evaluated in 12 Japanese adults. In Part C (randomized, double‐blind, crossover), the effects of single‐dose zuranolone 10 and 30 mg and placebo on electroencephalography parameters were evaluated in eight Japanese adults. Results Single and multiple doses of zuranolone were safe and well tolerated in all subjects. Linear pharmacokinetics were observed in the studied dose range. Time to steady‐state plasma concentration was within 72 h for Japanese and White adults. Pharmacokinetic profiles were comparable between Japanese and White adults and between Japanese adults and Japanese elderly subjects. Plasma exposures of zuranolone were greater in the fed versus fasted state. Single‐dose zuranolone 30 mg increased low‐beta electroencephalography power. Conclusion In healthy Japanese subjects, zuranolone was well tolerated; pharmacokinetic profile was unaffected by ethnicity or age; plasma exposures were greater in the fed state. The increased low‐beta electroencephalography power with the 30‐mg dose is consistent with γ‐aminobutyric acid receptor type A activation by zuranolone.